Assessment of Peripheral Neuropathy in Patients with β-Thalassemia via Electrophysiological Study: Reevaluation in the Era of Iron Chelators. (4th March 2018) - Bayhan, Turan; Ünal, Şule; Konuşkan, Bahadır; Erdem, Onur; Karabulut, Erdem; Gümrük, Fatma
Abstract: Peripheral neuropathy is one of the complications of β-thalassemia (β-thal) that has been investigated in limited reports. We aimed to detect the rate of peripheral neuropathy and risk factors for neuropathy development in patients with β-thal. The study was performed in patients with β-thal intermedia (β-TI) or β-thal major (β-TM). Prospective electrophysiological studies were achieved via standard procedures. A total of 27 patients were enrolled in the study. Electrophysiological studies for both motor and sensory nerves were within normal range. In motor nerve studies, delayed peroneal nerve latency was found in patients with high ferritin levels, increased ulnar nerve amplitude was detected in patients ≥20 years old, and increased tibial nerve amplitude was seen in patients with low copper levels. We could not show peripheral neuropathy in our patients. Increased ferritin level, older age, and copper deficiency may cause mild changes in electrophysiological studies of motor nerves.